Pemberdayaan ekonomi masyarakat rentan pasca kondisi new normal pada daerah rawan kebakaran hutan dan lahan gambut di Kabupaten Siak - Ashaluddin Jalil; Yesi Yesi; Seger Sugiyanto (Unri Conference Series: Community Engagement, 2020)
The economy of people in areas prone to forest and land fires after the new normal is very shaken because of the Covid-19 crisis and the dry season. This service was carried out in Kampung Rawa Mekar Jaya, Siak Regency with the aim of creating economic resilience for people living in areas prone to forest and land fires by managing peat using environmentally friendly methods or not using fire. The service method begins with preparation and implementation by involving elements of students and the local community. The community service activities include catfish farming and planting of family medicinal plants or TOGA. The achievement of community service can be seen from the enthusiasm of the community in participating in the entire process, from discussions to field actions. Meanwhile, service constraints were caused by covid-19, which limited time and movement and required rearranging program plans.